Dinamika Partai Politik Indonesia untuk Membangun Negara Hukum Indonesia yang Demokratis - Muhammad Thohir (Universitas Islam Negeri Raden Fatah Palembang, 2017)
Political party has position and important part of democration and rule of law systems. There are both of their correlation systems based on sovereignity. According to rule of law that secure human right, esspecially at freedom of political. Political party is one of democrationed media. So Romo Magnis suseno said that democration without rule of law unmeaning. Problem solving in these cases are what is mean of political party and how daoes political party build rule of law by democration principle. Conclusion that dynamical of Indonesian political party has tended to goverment power and did not look state interest itself. That tendension focuses to monopolized of goverment at the other sector. We knew that political party is tool of public aspiration to make good condition. It is one of intitutional which has ideal, vision, though and public care sense of democration. And in constructing democration of Rule of law system and good governance must be created by good public service, openes and accountability of state institutions. Because of them we must do rule of law and democrations principles. Example professional free press and educated.